Elevating Lower Extremity Reconstruction: An Algorithmic Approach to Free Flap Re-elevation - Nye, Jessica R.; Mitchell, David T.; Talanker, Michael T.; Hopkins, David C.; Wang, Ellen; Obinero, Chioma G.; Barrera, Jose E.; Greives, Matthew R.; Wu-Fienberg, Yuewei; Bhadkamkar, Mohin A. (Journal of Reconstructive Microsurgery, 2024)
Background Free flap (FF) reconstruction is frequently required for soft-tissue coverage after significant orthopaedic trauma of the lower extremity (LE). While usually the final step in limb salvage, re-elevation of the previously inset FF may be necessary to restore a functional limb. In this study, we present our algorithm for LE FF re-elevation and review our experience to identify factors associated with successful limb salvage and return to ambulation.Methods A retrospective, single-institution review was conducted of adult patients with LE wounds who required FF reconstruction from 2016 to 2021. From this cohort, patients who required re-elevation of their LE FF were identified. Successful FF re-elevation was defined by limb salvage and return to ambulation.Results During the study period, 412 patients with LE wounds required flap reconstruction. Of these patients, 205 (49.8%) underwent free tissue transfer, and 39 (9.5%) met our inclusion criteria. From this cohort, 34 had successful FF re-elevation, while 1 was non–weight bearing and 4 were elected for amputation due to chronic complications unrelated to their FF. Univariate analysis revealed the total number of FF re-elevations (p < 0.001), the frequency of re-elevation indicated for orthopaedic access (p < 0.001), and infections necessitating return to the operating room (p = 0.001) were each negatively associated with limb salvage and return to ambulation.Conclusion The described algorithm highlights the preoperative planning and meticulous flap preservation necessary for the successful coverage of critical structures following FF re-elevation. Our data demonstrate that LE FFs can be safely re-elevated for hardware access or flap revision. In these complex cases of LE trauma, management by a multidisciplinary team is essential for successful limb salvage.
Keywords: free flaps; microsurgery; reconstruction